Cutaneous involvement in COVID-19 patients - Beiu, Cristina; Ceausu, Emanoil; Popa, Mircea Ioan; Mihai, Mara Madalina; Popa, Liliana Gabriela; Popescu, Marius-Nicolae; Giurcaneanu, Calin (Revista română de boli infecţioase, 2020)
The ongoing coronavirus disease 2019 (COVID-19) outbreak was declared a pandemic by the World Health organization in early March 2020. The disease typically presents with viral respiratory symptoms that could progress to acute respiratory distress syndrome. Emerging evidence suggests different possible dermatologic manifestations of COVID-19, including: acral lesions (pernio-like, pseudo-chillblain), vesicular eruptions, macular and papular exanthema, urticaria, livedoid, purpuric and petechial rashes. However, specific skin manifestations of the COVID-19 disease have not yet been clearly established and the relationship between the appearance of skin lesions and SARS-CoV-2 infection is still unclear. These highly variable skin changes could represent a direct consequence of the viral infection, an immunological response to viral nucleotides, adverse reactions to drugs frequently used for the treatment of COVID-19, or other disorders. In a global effort to comprehend the exact cutaneous features of COVID-19, several international dermatological societies have initiated nationwide studies to analyze COVID-19 cutaneous manifestations during this pandemic. This paper represents a literature review of the scientific data available on the clinical characteristics and symptoms of the cutaneous manifestations associated with COVID-19. Such findings are extremely useful in establishing if dermatological manifestations in COVID-19 patients could harbor a diagnostic significance and subsequently be used as prognostic factors for outcomes of COVID-19.